2011
DOI: 10.1524/ract.2011.1819
|View full text |Cite
|
Sign up to set email alerts
|

Separation of lanthanides and actinides on a bistriazinyl pyridine coated reverse phase column

Abstract: The retention behaviour of uranium, thorium, americium and lanthanides has been investigated, using a reverse phase C 18 column modified with 2,6-bis(5,6-dipropyl-1,2,4-triazin-3-yl)pyridine (n-Pr-BTP) with the aim of investigating rapid lanthanide-actinide separations by HPLC technique. Nitric acid and α-hydroxy isobutyric acid (α-HIBA) have been employed as the mobile phase. The influence of mobile phase pH and concentration on the retention of metal ions has been studied. The aim of this study is to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…5−9 Fragments produced via C−N, C−O, C−H, and C−C bond cleavage in solution were identified for TODGA; 7,8 TEHDGA was shown to be more stable toward radiolysis. 9 It has been demonstrated that studies of the chemistry of gas phase ions can provide insights into condensed phase reaction mechanisms, and intermediates under solvent free conditions. 10,11 Using collision induced dissociation (CID), detailed information on the fragmentation of gas phase metal ion complexes can be obtained.…”
Section: ■ Introductionmentioning
confidence: 99%
“…5−9 Fragments produced via C−N, C−O, C−H, and C−C bond cleavage in solution were identified for TODGA; 7,8 TEHDGA was shown to be more stable toward radiolysis. 9 It has been demonstrated that studies of the chemistry of gas phase ions can provide insights into condensed phase reaction mechanisms, and intermediates under solvent free conditions. 10,11 Using collision induced dissociation (CID), detailed information on the fragmentation of gas phase metal ion complexes can be obtained.…”
Section: ■ Introductionmentioning
confidence: 99%
“… 45 Quite differently, the bistriazinyl pyridine-coated reverse phase column has been used as a stationary phase by Deepika et al to separate uranium, thorium, americium and Lns where nitric acid and α-hydroxy isobutyric acid (α-HIBA) was used as the mobile phases. 46 Furthermore, Raut et al described the RP-HPLC separation of Lns, Th 4+ and UO 2 2+ using n -octane sulfonate as a column modifier that exhibited partial cation exchanger property and hydrophobicity. 47 These methods and processes gave insights into the beautiful separation chemistry of chemically similar f-block elements.…”
Section: Introductionmentioning
confidence: 99%
“…This is also indicated by the large number of publications on newly developed extraction media and processes (e.g., see refs ). On the other hand, chromatographic separations are being considered again for preparative separation of REEs beside their classical use as analytical techniques (e.g., see refs ). In particular, the normal phase chromatographic mode , and ion exchange (IEX) or ion chromatography , have been considered.…”
Section: Introductionmentioning
confidence: 99%